Impact on staff of the Mentally Healthy Schools Framework - Anwar-McHenry, Julia; Drane, Cathy; Joyce, Phoebe; Donovan, Robert (Emerald, 2020)
Purpose: The Mentally Healthy Schools Framework (MHSF), based on the population-wide Act-Belong-Commit mental health promotion campaign, is a whole-school approach primarily targeting student mental health, but it is also intended for staff. This paper presents the results of an impact survey on staff after the implementation of the Framework in a number of schools in Western Australia.